UR_GERICHTE 2019_OG V 18 43. vom 28. Juni 2019 - UR Obergericht (2019)
Personalrecht. Art. 5 Abs. 2 und Art. 9 BV. Art. 322d Abs. 1 OR. Art. 91 Abs. 1, Art. 92 Abs. 1 und 2 und Art. 114 lit. c ZPO. Art. 37, Art. 52 und Art. 73 Abs. 1 PV. Kantonspolizei Korporal-Gradzulage.